2015
DOI: 10.1007/s00709-015-0793-6
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of microsporogenesis and microgametogenesis in Brachypodium distachyon

Abstract: Brachypodium distachyon has emerged as a model system for forage grass and cereal grain species. Here, we report B. distachyon pollen development at the ultrastructural level. The process of microsporogenesis and microgametogenesis in B. distachyon follows the typical angiosperm pollen development sequence. Pronounced evaginations of the nuclear envelope are observed prior to meiosis, indicating active nucleocytoplasmic exchange processes. The microspore mother cells undergo meiosis and subsequent cytokinesis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…This degeneration of the tapetum is normally classified as a type of programmed cell death (PCD) (Papini et al 1999), D r a f t and it has been recently reported that PCD in the tapetum of Brassica napus and Nicotiana tabacum are regulated by epigenetic changes, including an increase in global DNA methylation and MET1 expression (Solı´s et al 2014). As a result, G. celebica provides a normal pattern of pollen and tapetum development because the onset of tapetum degradation shares similarities with observations of most angiosperms, including as Brachypodium distachyon (Sharma et al 2015), Oryza sativa (Raghavan 1988), and Arabidopsis thaliana (Owen and Makaroff 1995). In contrast, the tapetum of G. mangostana began to degrade prior to meiosis, premature microspore mother cell degeneration was observed, microspore tetrads with complete callose deposition were rarely detected, and no pollen was observed at anthesis (Yapwattanaphun et al 2008;Nuanjunkong and Meesawat 2010).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This degeneration of the tapetum is normally classified as a type of programmed cell death (PCD) (Papini et al 1999), D r a f t and it has been recently reported that PCD in the tapetum of Brassica napus and Nicotiana tabacum are regulated by epigenetic changes, including an increase in global DNA methylation and MET1 expression (Solı´s et al 2014). As a result, G. celebica provides a normal pattern of pollen and tapetum development because the onset of tapetum degradation shares similarities with observations of most angiosperms, including as Brachypodium distachyon (Sharma et al 2015), Oryza sativa (Raghavan 1988), and Arabidopsis thaliana (Owen and Makaroff 1995). In contrast, the tapetum of G. mangostana began to degrade prior to meiosis, premature microspore mother cell degeneration was observed, microspore tetrads with complete callose deposition were rarely detected, and no pollen was observed at anthesis (Yapwattanaphun et al 2008;Nuanjunkong and Meesawat 2010).…”
Section: Discussionmentioning
confidence: 86%
“…The tapetum is of the secretory type, defined by the absence of a cell wall, and the tapetal protoplasts remaining in the parietal position of the locule until its complete degeneration (Pacini and Juniper 1979;Shivanna 2003). This type is considered to be a primitive characteristic due to its widespread occurrence in gymnosperms and angiosperms (Sharma et al 2015). The breakdown of tapetum took place after meiosis II, which corresponds with the complete encasement of callose walls around microspore tetrads.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, starch grains were involved in the formation of the callose wall and pollen intine. However, previous investigations demonstrated that the intine layer is deposited after mitosis (Sharma et al, 2015b). At the late microspore stage, starch grains began to accumulate in the microspores, and plentiful starch grains were present in the bicellular pollen.…”
Section: Discussionmentioning
confidence: 89%
“…Pollen grains were individually isolated in PCR tubes and germinated for PEP amplifications of whole genomes. The individual microspores, when treated with REPLI-g Single Cell Kit (QIAGEN) release genomic DNAs for subsequent amplifications [9]. All individually isolated cotton early free microspores released their contents giving adequate yields of amplified DNA products through multiple displacement amplification (MDA) technology.…”
Section: Whole Genome Amplification From Pollen and Microsporesmentioning
confidence: 99%
“…Microsporogenesis stages can allow the isolation of free microspores (immediately after the tetrad separation) when their tectum formation is discontinuous and before the initiation stage of endexine development [8,9]. Such microspores can easily be lysed with reagents used for DNA extractions from animal cells that only have cell membranes [10].…”
Section: Introductionmentioning
confidence: 99%